Saving the Commons in an Age of Plunder. (March 2016) - Batt, H. William
Abstract: Land ownership, as commonly understood today, originated with the enclosure movement during the English Tudor era almost four centuries ago. Karl Polanyi referred to this "propertization" of nature as the "great transformation." That land, water, and air was a social commons is now archaic and forgotten, and with it the classical economic concept of rent, which was, in theory, once paid to royalty as the earth's guardian. Garrett Hardin's article, "The Tragedy of the Commons, " raised alarm about the abuse and loss of this realm, and he recommended constraints and privatization to prevent this. Most people view titles to landed property much as they do their household goods, but Henry George saw that the earth should be seen as a common resource and its value taxed to benefit everyone. This would restore economic equilibrium to market exchanges and pay for government services. The capture of natural resource rents can supplant taxes on wages and capital goods, and it comports with all textbook principles of sound tax theory. This policy can be the modern replacement for the commons, and implementing resource rent capture is both economically and technically feasible.